The Banking and Financial Sector of Lao PDR : Financial Sector Note - Asian Development Bank (World Bank, Washington, DC, 2015)
During the second half of the 1980s, Lao PDR embarked on an ambitious program of economic reforms, called the New Economic Mechanism, whose main purpose was to gradually transform its centrally-planned economy into a market-oriented economy. The initial reform momentum lasted about one decade. The far-reaching reform program encompassed many critical components including: (a) promotion of private production through improved incentives; (b) institutional infrastructure to improve market economy operations; (c) the strengthening of Lao comparative advantages through trade liberalization and further specialization; and (d) the establishment of price stability through macroeconomic policy measures. The systemic changes introduced in Lao PDR have contributed to a significant transformation of the country s economic system, away from a rigorously centrally-planned economy and towards a form of market economy based on private ownership. The percentage of poor declined based on the national poverty line from 45 to 39 percent between 1992-93 and 1997-982. But the percentage of very poor did not decline and remained at slightly above 30 percent evidencing the need for even broader and faster growth. Moreover, several factors slowed down the economic liberalization process. Such factors included the lack of transparency in government-business relations, a weak civil society, the position of some interest groups at the national and provincial levels, and the existence of noncompetitive economic structures with a few firms and actors accounting for a large share of domestic production (except in agriculture). In some areas, reform policy stagnated and is lagging. This is the case in the financial sector. The creation of a two-tier banking system in the early 1990s with separate and well-defined functions for the central bank and the state-owned commercial banks, has not resulted in the expected benefits: Lao PDR is still suffering from chronic macroeconomic instability and the state-owned commercial banks are suffering from a large amount of non-performing loans. Taking into consideration the objective of the Lao leaders to improve the well-being of the Lao People, this paper argues that there are valid reasons for establishing rules that discipline the political influence on the design and conduct of economic policy, and more specifically, policy regulating the financial sector.